Kainic acid lesions to the lateral tegmental field of medulla: effects on cough, expiration and aspiration reflexes in anesthetized cats - Jakus, J; Stránsky, A; Poliacek, I; Baráni, H; Bosel'ová, L (Physiological research, 2000)
We have tested the hypothesis that neurons of both the ventral reticular nucleus and the adjacent parts of the lateral tegmental field (LTF) may be important for the production of motor programs associated with cough, expiration and aspiration reflexes. Our studies were conducted on non-decerebrate, spontaneously breathing cats under pentobarbitone anesthesia. Dysfunction of the medullary LTF region above the obex, produced by uni- or bilateral injections of kainic acid (a neurotoxin), regularly abolished the cough reflex evoked by mechanical stimulation of both the tracheobronchial and laryngeal regions and in most cases also the expiration reflex induced from the glottal area. However, some electrical activity still occurred in the neurogram of the recurrent laryngeal nerve during probing the laryngeal and glottal regions. Interestingly, the aspiration reflex elicited from the nasopharynx regularly persisted, although with lower intensity after the LTF lesion. Nevertheless, successive midcollicular decerebration performed in four cats also abolished the aspiration reflex. These experiments demonstrate the importance of medullary LTF neurons for the normal occurrence of cough and expiration reflexes. One possible explanation for the elimination of these expulsive processes is that the blockade of the LTF neurons may remove an important source of a facilitatory input to the brainstem circuitries that mediate cough and expiration reflexes. In addition, the potential importance of the mesencephalic reticular formation for the occurrence of the aspiration reflex and the role of the LTF in modulating both the eupnoeic breathing and the blood pressure are also discussed.
Keywords: Reticular Formation; Physical Stimulation; kočky; Kainic Acid; mechanika dýchání; čtvrtá mozková komora; agonisté excitačních aminokyselin; Medulla Oblongata; Female; Reflex; mezencefalon; zvířata; medulla oblongata; Electromyography; retikulární formace; anestezie; Fourth Ventricle; decerebrační rigidita; Excitatory Amino Acid Agonists; ženské pohlaví; fyzikální stimulace; krevní tlak; reflex; Male; Nerve Degeneration; degenerace nervu; Respiratory Mechanics; Cough; Anesthesia; kyselina kainová; Cats; kašel; Animals; Decerebrate State; mužské pohlaví; Blood Pressure; elektromyografie; Mesencephalon